Multilevel analysis of individual- and community-level determinants of birth certification of children under-5 years in Nigeria: evidence from a household survey - Uchechi Shirley Anaduaka (BMC, 2022)
Abstract Promoting birth certification is central to achieving legal identity for all - target 16.9 of the 2030 Sustainable Development Goals. Nigeria is not on track to achieve this goal with its low coverage of birth certification (BC). This study is aimed at identifying patterns of BC and its associated individual- and community-level factors, using pooled cross-sectional data from three rounds (2008, 2013, and 2018) of the nationally representative Nigerian Demographic and Health Survey. A weighted sample of 66,630 children aged 0-4 years was included, and a two-level multilevel logistic model which accommodates the hierarchical nature of the data was employed. Of the total sample, 17.1% [95% CI: 16.3-17.9] were reported to be certified. Zamfara state (2.3, 95% CI: 0.93-3.73) and the Federal Capital Territory (36.24, 95% CI: 31.16-41.31) reported the lowest and the highest BC rates. Children with an SBA [AOR = 1.283, 95% CI: 1.164-1.413] and with at least one vaccination [AOR = 1.494, 95% CI: 1.328-1.681] had higher odds of BC. The AOR for mothers with at least one prenatal visit was 1.468 [95% CI: 1.271-1.695], and those aged 30-34 years at the time of birth [AOR = 1.479, 95% CI: 1.236-1.772] had the highest odds. Further, the odds of BC increased the most for mothers [AOR = 1.559, 95% CI: 1.329-1.829] and fathers [AOR = 1.394, 95% CI: 1.211-1.605] who were tertiary-educated. In addition, children in middle-income [AOR = 1.430, 95% CI: 1.197-1.707] or rich wealth HHs [AOR = 1.776, 95% CI: 1.455-2.169] or those whose families had bank accounts [AOR = 1.315, 95% CI: 1.187-1.456] had higher odds. Living in non-poor and within close proximity to a registration center (RC) act as protective factors for BC, while living in poor communities [AOR = 0.613, 95% CI: 0.486-0.774] and more than 10kms from an RC reduce the odds of BC [AOR = 0.466, 95% CI: 0.377-0.576]. The study identified several protective and risk factors which policymakers can adopt as strategic areas for universal birth certification. National and sub-national programs should integrate non-formal institutions as well as target child and maternal utilization of healthcare services to promote BC in Nigeria.